Fungsi Media Sosial Sebagai Sarana Informasi Haji Dan Umroh Di Kementerian Agama Kabupaten Lampung Selatan - Masrur, Ghufran; Fatmawati, Amanda; Liza, Sindi Nurma; Haq, Dliyaul (Jurnal Dewantara, 2024)
The rapid advancement of technology and information has brought many impacts on daily life, including the use of social media. One of the functions of social media is as a means of information, which is utilized by the Ministry of Religious Affairs of South Lampung Regency to provide information about Hajj and Umrah. The aim of this research is to examine how social media functions as a source of information for Hajj and Umrah at the Ministry of Religious Affairs of South Lampung Regency. This research was conducted at the Office of the Ministry of Religious Affairs of South Lampung Regency. This type of research is qualitative descriptive. The informants in this study are the head of the Ministry of Religious Affairs Office of South Lampung Regency, the head of the hajj and umrah organizing section, and the staff managing the social media accounts. The techniques used in data collection are interviews, observations, and documentation. Based on the research conducted, it can be concluded that there are four functions of social media as a means of information for Hajj and Umrah first information second, sharing, third relationship and fourth group. Pesatnya kemajuan teknologi dan juga informasi telah membawa banyak dampak dalam kehidupan sehari-hari, termasuk juga dalam penggunaan media sosial, salah satu fungsi dari media sosial adalah sebagai sarana informasi hal inilah yang dimanfaatkan oleh Kemeterian Agama Kabupaten Lampung Selatan. menggunakan media sosial sebagai sarana informasi haji dan umroh. Tujuan dari penelitian ini adalah bagaimana fungsi media sosial sebagai sarana informasi haji dan umroh di Kemeterian Agama Kabupaten Kabupaten Lampung Selatan. Penelitian ini dilakukan di Kantor Kemeterian Agama Kabupaten Lampung Selatan. Jenis penelitian ini adalah deskriptif kualitatif. Kemudian informan dalam penelitian ini adalah kepala Kantor Kemeterian Agama Kabupaten Lampung Selatan, kepala seksi penyelenggara haji dan umroh, serta petugas yang mengelola akun media sosial. Adapun teknik yang digunakan dalam pengumpulan data adalah wawancara, observasi dan juga dokumentasi. berdasarkan penelitian yang dilakukan dapat disimpulkan bahwa terdapat 4 fungsi media sosial sebagai sarana informasi haji dan umroh yaitu pertama informasi, yang kedua sharing, yang ketiga relationship, yang keempat group.